Morphological Variation of Asian Small Lizards genus Tytthoscincus Linkem, Diesmos & Brown (Squamata : Scincidae) in Indonesia - Firmansyah, Richo; Riyanto, Awal; Kurniawan, Nia (The Journal of Experimental Life Science, 2023)
Morphological variations in species with a relatively broad distribution, including the genus Tytthosincus, were likely a result of island isolation. This research was conducted to map the morphological variations of the genus Tytthoscincus in Indonesia. A total of 32 specimens of the Tytthoscincus scientific collection in the Zoologicum Bogoriense Museum (MZB) - National Research and Innovation Agency (BRIN) and identified as T. temmincki, T. textus, and T. parvus have been examined and data collection which includes six morphometric characters and 12 meristic characters. Morphometric data were analyzed in univariate and multivariate. Univariate analysis was carried out by the Kruskal-Wallis test, while multivariate analysis was done with the Principal Component Analysis (PCA) test. The results showed morphology in T. temmincki and T. textus, namely the number of loreal scales and tympanum diameter. Both T. temmincki and T. textus consist of two groups, but the morphological variation in T. temmincki and T. textus in this study has yet to provide certainty as a different species. However, one was T. textus Type 2, isolated from other species on Jampea Island, Sulawesi. Further research was needed to clarify the taxonomic status of these variations by increasing the number of adequate samples supported by the molecular analysis approach. Keywords: meristic, morphometric, species, Tytthoscincus, variation.